Do green bonds perform differently than conventional bonds during market stress - Gerhardt, Marie-Christine (2021)
Using a two-fold focus on abnormal return and bond liquidity, this thesis investigates whether green bonds and conventional bonds perform differently during market stress by analyzing 134green and 134conventional matched bonds. This study finds that investor preferences do not change during market stress in general, as the abnormal return of green and conventional bonds appear to co-move. Upon further scrutiny it is, however, confirmed that geopolitical infrastructure as well as industry specific characteristics lead to diverging performances among bond pairs, thus, impact investor choices in specific regions and sectors. Contrary, ESG indicators show little impact on bond performance.